Peran Mata Pelajaran PKN Dalam Membangun Karakter Anak Sekolah Dasar Pada Kehidupan Sosial - Wahidah Destiani Pulungan (Educational Journal, 2026)
This study aims to identify the role of the subject of Civic Education (PKn) in shaping the character of elementary school children, with a focus on their social life context. The background of this research is based on concerns regarding the decline in the character quality of the younger generation, which is evident from the high rates of behavioral deviations among students. This phenomenon is often linked to the low development of character during the educational process. This research employs a qualitative approach with a descriptive study method, including participatory observation, interviews, documentation studies, and literature reviews. The findings indicate that the implementation of PKn is often suboptimal, focusing more on academic content mastery rather than the application of values in daily life. Therefore, innovation in PKn  teaching is necessary to connect theory with practice and to enhance students' awareness of the importance of civic values. With a better understanding of the role of PKn, it is hoped that more effective strategies can be found to shape a qualified and integrity-filled younger generation.